Electroacupuncture Ameliorates Cognitive Impairment through Inhibition of Ca2+-Mediated Neurotoxicity in a Rat Model of Cerebral Ischaemia–reperfusion Injury. Issue 6 (December 2018) - Zhang, Yun; Mao, Xiang; Lin, Ruhui; Li, Zuanfang; Lin, Jing
Background: The hippocampus is vulnerable to severe damage after cerebral ischaemia–reperfusion (I/R) injury. This study aimed to explore the effect of electroacupuncture (EA) on cognitive impairment and its relationship with Ca 2+ neurotoxicity in a rat model of I/R injury induced by middle cerebral artery occlusion (MCAO). Methods: 60 adult male Sprague-Dawley rats were randomly divided into three groups: control (sham surgery) group, untreated MCAO group and EA-treated MCAO+EA group. Rats in the MCAO and MCAO+EA groups underwent modelling of poststroke cognitive impairment by MCAO surgery. EA was performed for 30 min daily at GV20 and GV24 (1–20 Hz) for 1 week. The Morris water maze experiment was used to assess cognitive function. 2, 3, 5-triphenyl tetrazolium chloride staining was used to measure infarct volume. The intracellular Ca 2+ content in the Cornu Ammonis (CA)1 area of the hippocampus was assessed by laser confocal scanning microscopy. ELISA was performed to evaluate the concentration of glutamate (Glu) in the hippocampus, and the protein expression of two Glu receptors (N-methyl-D-aspartic acid receptor (NMDAR) 2A and NMDAR2B) were analysed by Western blotting. Results: Compared with the untreated MCAO group, EA effectively ameliorated cognitive impairment (P=0.01) and shrunk the infarct volume (P=0.032). The content of intracellular Ca 2+, Glu and NMDAR2B in the hippocampus was significantly raised by MCAO (P=0.031-0.043), while EA abrogated these effects. NMDAR2A was decreased by MCAO (P=0.015) but increased by EA (P=0.033). Conclusions: EA had a beneficial effect on cognitive repair after cerebral I/R, and its mechanism of action likely involves a reduction of Ca 2+ influx via inhibition of Glu neurotoxicity and downregulation of NMDAR2B expression.